Two Repressor Elements Inhibit Expression of the von Willebrand Factor Gene Promoter In Vitro - Ardekani, Ali M.; Greenberger, Joel S.; Jahroudi, Nadia (Thrombosis and Haemostasis, 1998)
A fragment of the human von Willebrand factor (VWF) gene promoter corresponding to sequences –487 to +247 bp functions as an endothelial specific promoter in cell culture. We have previously reported that a GATA transcription factor functions as an activator and an NF1 like protein functions as a repressor of this promoter fragment. We have now identified a second negative regulatory element in the VWF promoter that interacts with nuclear factor(s) (designated R) in both bovine aortic endothelial and smooth muscle cells. Inhibition of either the NF1 or the R repressor alone is not sufficient to activate the VWF promoter in smooth muscle cells. The present studies reveal that simultaneous inhibition of both repressors activates the VWF promoter in smooth muscle cells. The data support a model of selective derepression to explain the endothelial cell specific activity of the –487 to +247 fragment of the VWF promoter in vitro.